Elder Mistreatment in U.S. Community-Dwelling Chinese Older Women. (August 2016) - Dong, XinQi; Chen, Ruijia; Simon, Melissa A.
This study explored the prevalence and correlates of elder mistreatment among community-dwelling Chinese women in the U.S. Data were from the Population Study of Chinese Elderly in Chicago (PINE), a population-based study of U.S. Chinese older adults aged 60 years and above. Of the 1, 833 older women, 289 (15.8%) reported suffering from elder mistreatment. Higher educational levels, lower overall health status, and worsening health over the past year were positively correlated with elder mistreatment, while a greater number of children and grandchildren were negatively correlated with elder mistreatment. Considerable efforts should be put into designing tailored interventions to reduce elder mistreatment in U.S. Chinese women.